2016
DOI: 10.1192/bjp.bp.115.163543
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style in childhood and mortality risk at older ages: a longitudinal cohort study

Abstract: Background Parenting style is associated with offspring health, but whether it is associated with offspring mortality at older ages remains unknown. Aims We examined whether childhood experiences of suboptimal parenting style are associated with increased risk of death at older ages. Method Longitudinal cohort study of 1,964 community-dwelling adults aged 65 to 79 years. Results The association between parenting style and mortality was inverse and graded. Participants in the poorest parenting style score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
(71 reference statements)
1
27
1
Order By: Relevance
“…Research on the association between childhood experiences of parenting and cancer development in late adulthood is very limited. A study of 913 US middle-aged male physicians found that poor-quality father–son relationship, but not mother–son relationship, was associated with an increased risk of incident cancer (Shaffer et al 1982 ), while a recent study found a negative dose–response association between parenting quality and cancer mortality risk in people aged 65–79 years (Demakakos et al 2016b ). Evidence also suggests an association between childhood experiences of abuse and neglect and an increased risk of cancer in early and mid-adulthood (Brown et al 2010 , 2013 ; Norman et al 2012 ; Morton et al 2012 ; Kelly-Irving et al 2013a ; Hyland et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on the association between childhood experiences of parenting and cancer development in late adulthood is very limited. A study of 913 US middle-aged male physicians found that poor-quality father–son relationship, but not mother–son relationship, was associated with an increased risk of incident cancer (Shaffer et al 1982 ), while a recent study found a negative dose–response association between parenting quality and cancer mortality risk in people aged 65–79 years (Demakakos et al 2016b ). Evidence also suggests an association between childhood experiences of abuse and neglect and an increased risk of cancer in early and mid-adulthood (Brown et al 2010 , 2013 ; Norman et al 2012 ; Morton et al 2012 ; Kelly-Irving et al 2013a ; Hyland et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of retrospectively collected data on parenting experiences and childhood SEP makes our study susceptible to measurement bias. Nevertheless, these data are known to have good predictive validity and be inversely associated with morbidity and mortality in ELSA (Demakakos et al 2012 , 2016a , b ). Attrition and non-response may have biased to some extent our results (see eTable 5) and likely make our findings a conservative account of the true association between parenting experiences and cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Closer examination of parenting styles [410,411,412] in the urban grey space context, positive psychology interventions (also mindfulness, empathy, and relaxation response training) [413,414,415,416,417,418], and encouragement of time spent in natural environments via large-scale nature engagement campaigns [419,420] are worthy of study. We also need to learn more concerning emerging microbial applications in early life (e.g., through nature contact, controlled seeding of microbes and via environmental design) [421,422,423].…”
Section: Discussionmentioning
confidence: 99%